Experimental and modelling study of low velocity impacts on composite sandwich structures for railway applications. (October 2016) - Sakly, Adnene; Laksimi, Abdelouahed; Kebir, Hocine; Benmedakhen, Salim
Abstract: This paper aims to evaluate the damage resistance of sandwich composites used in train structures subjected to low velocity impacts. These impacts can be induced by railway ballast projection incidents underneath the floor of the train. A high-speed and low weight test bench to simulate such impacts was developed in our laboratory. After the impact, the damage mechanism evolution as a function of solicitation conditions was inspected. Three-dimensional finite element models were implemented to analyze the impact response. Results obtained from numerical simulations have confirmed experimental observations. Shock wave propagation localized around the impact point confined the damage. Visual inspection identified delamination in composite skin, fiber breakage, and indentation. Skin/core debonding, core crushing and shear failure were analyzed. Damages intensified proportionally with the number of successive projectile launches. Correlations between impact energy and damage mode are discussed. Highlights: A high-speed and low weight test bench to simulate ballast impacts was developed. Shock wave propagation localized around the impact point confined the damage. Delamination and matrix cracking appeared to be the main damage modes. Delamination defect sizes increased during successive launches for all − 45°/90° interfaces.